Multiple trusted devices seamless authentication scheme / Qatrunnada Abdul Rahman - Abdul Rahman, Qatrunnada (2017)
Ubiquitous computing paradigm is a significant progression of computing technology as it has changed the way computing hardware and devices are being set up and used in the surrounding infrastructures. Moreover it mostly populated with smart mobile devices which have networking capability and sensors. Its dynamic and volatile nature also brought many challenging issues in security implementations, particularly on how to provide an appropriate authentication scheme for devices and applications. Therefore authentication services are expected to focus on device to device interaction which is seamless and autonomous instead of user to device interaction which requires human participation. Furthermore, devices in such environment are said to be exposed to attacks such as identity impostor, unauthorized access and also man-in-the-middle attacks. For that reason, through this research an authentication scheme is developed, not only to ensure device's authenticity but also provides seamless authentication without either needing password login or human participation. This condition is achieved by employing a trusted device to authenticate another device seamlessly. Accordingly, the requirements for the proposed authentication scheme are trust and seamlessness. The authentication scheme was developed as a mobile application using Java and was implemented on Android platform. The authentication scheme has been successfully tested on a test-bed using smartphones. In conclusion, it is hoped that this study may establish a new research dimension in the security domain along with contributing towards safeguarding devices' authenticity and the information being shared in a Ubiquitous computing environment as well as enabling seamless device to device authentication.